Winter dumps on Eldorado mining claims waiting to be washed in the Spring, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Winter mining, showing dumps on Eldorado" Klondike Gold Rush.